Search for E. coli O157 and non-O157 in sausages and blood sausages produced and/or marketed in the Northwest of the province of Buenos Aires, Argentina: Search for E. coli O157 and non-O157 in sausages and blood sausages produced and/or marketed in the Northwest of the province of Buenos Aires, Argentina (Veterinary Science, 2025)
A search was conducted for toxigenic E. coli O157 and non-O157 strains present in samples of sausage and blood sausage produced and/or sold in the city of Junín, Buenos Aires province, Argentina. The outlets where these products were sold in the city were identified, and representative samples of these products sold in different neighborhoods were taken. The samples were analyzed using the selective differential enrichment and isolation methodology proposed in USDA/FSIS: 2010. In the isolated strains, the presence of the stx1, stx2, and rfbO157 genes corresponding to the toxins produced by STEC strains and the gene exclusive to serogroup O157, respectively, was confirmed by PCR. E. coli strains with at least one of the investigated genes were detected in 17 of the 25 fresh sausages samples analyzed (65%). In the case of blood sausage samples, 5 of the 25 samples studied (20%) had E coli strains with at least one of the aforementioned genes
Keywords: Fresh sausages; Blood sausages; Toxigenic E. coli